1874. Adherence to Practice Guidelines for Treating Diabetic Foot Infections: An Opportunity for Syndromic Stewardship. (26th November 2018) - McCreery, Randy; Bergman, Scott; Vanschooneveld, Trevor
Abstract: Background: Adherence to the Infectious Diseases Society of America (IDSA) guidelines for the treatment of diabetic foot infections (DFIs) has been associated with improved outcomes. Yet, compliance with these guidelines has been reported to be low. We initiated a quality improvement project aimed at improving guideline adherence for DFI management. Baseline results are reported here. Methods: We reviewed all hospitalized primary DFIs newly initiated on antibiotics over 1 year (July 2014–June 2015). We collected demographics, DFI severity per IDSA guidelines, antibiotic use, and microbiology data. Guideline adherence for culturing and empiric antibiotic choice (based on severity) was assessed per IDSA guidelines. We then created an institutional guideline and electronic order set with built-in clinical decision support. Educational lectures on DFI best practices were given to providers who commonly treat DFIs. Results: One hundred seventy-seven DFI admissions were identified: 40% severe ( n = 70), 47% moderate ( n = 84), 8% mild ( n = 14), and 5% with no evidence of infection ( n = 9). Demographics: mean age 58 years; 68% male, mean HgbA1c 8.6%, length of stay 6.9 days, 3-year mortality 13%. Empiric antibiotic regimens were judged inappropriate in 36% (64/177) of cases. The most common reason for inappropriate antibiotic use was unnecessary coverage for Pseudomonas aeruginosa in 50% (54/107) of nonsevere cases. In 28% (39/140) of cases with an ulcer, wound or skin breakdown, a superficial swab culture was obtained which is inappropriate. Only 33.3% ( n = 56) had a deep tissue culture obtained. In patients with deep tissue cultures, methicillin-resistant Staphylococcus aureus (MRSA) was found in 11% (6/56) of cases but covered for empirically in 88% (50/56). Pseudomonas was found in 2% (1/56) of cases but covered for empirically in 73% (41/56). Conclusion: MRSA and Pseudomonas are uncommon DFI pathogens yet are frequently treated empirically. Inappropriate antibiotic use is often due to empiric coverage for Pseudomonas in nonsevere DFIs where it is a rare pathogen. Culture practices are also less than ideal with frequent superficial swabs and underutilization of deep cultures. Institutional guidelines were developed to specifically address these issues and data collection of the impact of this project is in process. Disclosures: S. Bergman, Merck: Grant Investigator, Grant recipient. T. Vanschooneveld, Merck: Grant Investigator, Grant recipient.